Optimizing Village-Owned Enterprises as Legal Entities in Efforts to Enhance Cooperation and Asset Management - Ikhwansyah, Isis; Faisal, Pupung; Trisnamansyah, Purnama (Jurnal Bina Mulia Hukum, 2024)
Village-Owned Enterprises (BUM Desa) is a business entity that carries out business in the economic sector and/or public services. The status of BUM Desa is confirmed as a legal business entity in the Law on Job Creation. This article discusses efforts that can be made to optimize the legal entity status of BUM Desa after the enactment of the Law on Job Creation to increase cooperation and management of BUM Desa assets after the enactment of the Job Creation Law. The research method used is normative juridical, namely research based on legal sources and their findings. The research results show that first, determining the legal entity status of BUM Desa has implications for optimizing the intensity of cooperation with third parties. Clarity on the legal entity status of BUM Desa can optimize opportunities for BUM Desa cooperation with third parties, because third parties will feel more secure in collaborating with legal entities as legal subjects who have separate assets. Second, after the establishment of BUM Desa as a legal entity, it is necessary to manage BUM Desa assets separately from Village assets, based on the statutory regulations governing BUM Desa, Good Corporate Governance Principles, and internal regulations of BUM Desa, as well as cooperation agreements with third parties if the object of cooperation is BUM Desa assets.